Emotional Intelligence and Employees Job Performance of Commercial Banks in Pokhara Metropolis - Lamichhane, Baburam; Subedi, Madhab Prasad (Journal of Interdisciplinary Studies, 2026)
The study explores the behaviour constructs of emotional intelligence and job performance of the employees working in the commercial banks of Pokhara Metropolitan City, Nepal, with the aim to find out the impact of emotional intelligence on their job performance. In this study, emotional intelligence has been considered by defining its various dimensions such as self-awareness, self-regulation, motivation, empathy, and social skills. Job performance, meanwhile, has been measured in terms of task performance and contextual performance. The study applied the method of simple random sampling for the selection of 249 participants for analysis from eight different commercial banks in Pokhara. Primary data were collected directly from employees working in commercial banks in Pokhara through structured questionnaires administered via Google Forms according to the theoretical model of Goleman on emotional intelligence. Data have been analyzed using multiple regression technique by employing SPSS software version 25. The findings of the study revealed that emotional intelligence has a statistically significant positive impact on job performance, and social skills emerged as the most important predictor. Similarly, manager empathy and self-regulation were found comparatively insignificant. The analysis revealed that there is a significant effect of the dimensions of emotional intelligence on performance at work. This study provides practical recommendations for banking executives and human resource managers in order to improve the efficiency and effectiveness of the workforce of Nepali commercial banks.